Natural resources and conflicts in the changing international system - Kakonen, Jyrki (Aldershot, 1988)
In retrospective analyses there is always the risk that you highlight only those developments that are important to the outcome. This is something I have consciously tried to avoid in this book, in which I shall be looking back at trends and developments in the international system of the 1970s. It is not however my intention to write the whole history of international politics of the 1970s; instead, I focus on three selected phenomena and their mutual connec tions. These are primarily discussed against the background of the contem porary international setting, but also from a longer historical perspective.
Keywords: Natural resources